Ultrafiltration - an alternative method to polyethylene glycol precipitation for macroprolactin detection - Beda-Maluga, Karolina; Pisarek, Hanna; Romanowska, Irena; Komorowski, Jan; Świętosławski, Jacek; Winczyk, Katarzyna (Archives of medical science, 2015)
The aim of the study was to evaluate two methods of macroprolactin (MaPRL) detection - precipitation with polyethylene glycol (PEG) and ultrafiltration and to compare these techniques with "gold standard" - gel filtration chromatography (GFC). The study was conducted on 245 patients - 45 with organic and 200 with functional hyperprolactinaemia. In all the subjects MaPRL was detected by precipitation with PEG and ultrafiltration. Additionally, gel filtration chromatography was performed in some of the serum samples. Macroprolactinaemia was detected in 27 patients - 8 with prolactinoma and 19 with functional hyperprolactinaemia. Assessing positive and negative results for MaPRL, we observed high diagnostic agreement (95.9%) and positive correlation (r = 0.506, p < 0.001) between the methods. The results of precipitation and ultrafiltration positive for MaPRL were concordant in 63%. The dominance of MaPRL detected with precipitation and/or ultrafiltration was confirmed by GFC in 76% of cases (all patients with functional hyperprolactinaemia). Among 6 examined patients with prolactinoma, GFC showed four false-positive results - 1 case of precipitation and 3 cases of ultrafiltration. Efficacy of MaPRL detection with precipitation and ultrafiltration is comparable especially in cases of functional hyperprolactinaemia. In patients with prolactinoma, precipitation seems to be a more efficient separation method.